2006
DOI: 10.1111/j.1365-2648.2006.04029.x
|View full text |Cite
|
Sign up to set email alerts
|

Health preferences and decision‐making needs of disadvantaged women

Abstract: The majority of disadvantaged women were actively involved in decision-making and needed decision support to navigate the healthcare system. Nurses should play a more pivotal role in providing health decision support. This study needs to be replicated in other countries and cultural contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A classification of information needs was generated based on the typology of information needs in persons with severe mental disorders as proposed by Mueser and colleagues . Moreover, a classification scheme for ‘identified decisions’ was developed based on the categorization used in a needs assessment study from Bunn and colleagues that investigated decision‐making needs among disadvantaged women with a wide range of diagnoses and decisional settings. No other category of decision‐making needs was accounted for in the classification scheme as only two of the four included studies on decision‐making needs investigated decision‐making needs based on the ODSF including the categories decision‐making role, decisional conflict, decision‐making behaviour, support and resources, and mode of delivery …”
Section: Methodsmentioning
confidence: 99%
“…A classification of information needs was generated based on the typology of information needs in persons with severe mental disorders as proposed by Mueser and colleagues . Moreover, a classification scheme for ‘identified decisions’ was developed based on the categorization used in a needs assessment study from Bunn and colleagues that investigated decision‐making needs among disadvantaged women with a wide range of diagnoses and decisional settings. No other category of decision‐making needs was accounted for in the classification scheme as only two of the four included studies on decision‐making needs investigated decision‐making needs based on the ODSF including the categories decision‐making role, decisional conflict, decision‐making behaviour, support and resources, and mode of delivery …”
Section: Methodsmentioning
confidence: 99%
“…This semi‐structured interview guide was used in previous needs assessment studies for a national survey in Canada (O'Connor et al . 2003b), as well as for disadvantaged Chilean women (Bunn et al . 2006) and disease‐specific populations such as individuals with HIV/AIDS, cancer and palliative care (Stacey et al .…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, the Framework for Decision Coach‐Mediated Shared Decision Making is transferable across clinical environments, patient populations, and countries. Studies conducted in different countries indicate that patients want to participate in making health decisions and an abundance of decisions across clinical settings that are innately challenging given the need to weigh the benefits and risks across options (O'Connor et al 2003, 2007; Bunn et al 2006; Doull et al 2006). Our clinical and research experiences in Canada, United States, United Kingdom, Australia, and Chile have shown that decision coaching for patients and/or family members can address modifiable factors influencing decisional conflict to ensure patients are informed, clear about their values associated with the options, and supported in decision making.…”
Section: Development Of Decision Coaching Competenciesmentioning
confidence: 99%